A new approach in modeling AC flashover voltage for polluted insulator - Jaafar S.; Ahmad A.S.; Ghosh P.S.; Aljunid S.A.K. (2023)
Contamination-driven insulator failure is a problem that incessantly plagues distribution system. It erodes power quality and diminishes system reliability. Research on insulator pollution is directed primarily to understand the physics of the growth of discharge and to develop a mathematical model, which can predict the critical flashover voltage and current. In this paper a new ac model for flashover voltage has been proposed taking into consideration "Equivalent Salt Deposit Density (ESDD)" in place of "Resistance per unit Length". The salient feature of the proposed model is that it takes into account the selection of an appropriate value of the proposed "Pollution Severity Factor" which varies with the "salt present in the pollution layer" and "width of the pollution channel". The proposed model has been validated against experimental results taken from an experiment carried out on a flat plate model. It has been observed that the modeled results closely follow the experimental curves and can predict rms value of critical flashover voltage with a mean absolute error (MAE) of < 5.00%. The effectiveness of the model was also verified by comparing the modeled results against the experimental and theoretical results of other researchers and good agreement has been obtained.